Multisample motif discovery and visualization for tandem repeats - Zhang, Yaran; Hulsman, Marc; Salazar, Alex; Tesi, Niccolò; Knoop, Lydian; van der Lee, Sven; Wijesekera, Sanduni; Krizova, Jana; Kamsteeg, Erik-Jan; Holstege, Henne (Genome Research, 2025)
Tandem repeats (TRs) occupy a significant portion of the human genome and are a source of polymorphisms due to variations in sizes and motif compositions. Some of these variations have been associated with various neuropathological disorders, highlighting the clinical importance of assessing the motif structure of TRs. Moreover, assessing the TR motif variation can offer valuable insights into evolutionary dynamics and population structure. Previously, characterizations of TRs were limited by short-read sequencing technology, which lacks the ability to accurately capture the full TR sequences. As long-read sequencing becomes more accessible and can capture the full complexity of TRs, there is now also a need for tools to characterize and analyze TRs using long-read data across multiple samples. In this study, we present MotifScope, a novel algorithm for the characterization and visualization of TRs based on a de novo k-mer approach for motif discovery. Comparative analysis against established tools reveals that MotifScope can identify a greater number of motifs and more accurately represent the underlying repeat sequences. Moreover, MotifScope has been specifically designed to enable motif composition comparisons across assemblies of different individuals, as well as across long-read sequencing reads within an individual, through combined motif discovery and sequence alignment. We showcase potential applications of MotifScope in diverse fields, including population genetics, clinical settings, and forensic analyses.
10.1101/gr.279278.124